2015
DOI: 10.1016/j.biocon.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and visitor management in a thousand protected areas in China

Abstract: a b s t r a c tChina has $8000 protected areas, with different categories and levels of designation. These include many reserves of global conservation significance. There are more numerous but smaller parks in the more heavily populated provinces of the south and east, and fewer larger parks in the northwest. We sampled 1200 representative parks nationwide, using questionnaires delivered to park managers in person, with 160 categorical or ordinal parameters. Response rate was 92.5%. We carried out three analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…Much of the new funding has gone toward infrastructure improvements, particularly infrastructure to accommodate visitors. Some of these infrastructure projects have been dramatic-e.g., cableways (present in 10% of protected areas nationally) and high elevators (up to 330 m at Wulingyuan) (Zhong et al, 2015). Visitation to national nature reserves has also increased substantially .…”
Section: Substantial Government Investmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Much of the new funding has gone toward infrastructure improvements, particularly infrastructure to accommodate visitors. Some of these infrastructure projects have been dramatic-e.g., cableways (present in 10% of protected areas nationally) and high elevators (up to 330 m at Wulingyuan) (Zhong et al, 2015). Visitation to national nature reserves has also increased substantially .…”
Section: Substantial Government Investmentmentioning
confidence: 99%
“…Whereas some reserves have received substantial funding-particularly the oldest and most visited reserves-surveys of managers and individual case studies reveal that many are underfunded relative to their needs (Zhong et al, 2015). Surveys across 1000 protected areas of all types, not just national nature reserves, found that 25% have annual revenues above US$771,000 (5 million CNY), whereas 38% operate on less than US$77,000 (500,000 CNY) and 11% on less than US$7700 (50,000 CNY) (Zhong et al, 2015).…”
Section: Substantial Government Investmentmentioning
confidence: 99%
See 3 more Smart Citations